Strategi pengelolaan permintaan ekonomi sirkular pada tempat penampungan sampah sementara studi Bintaro, Ampenan Utara - Septiya Fahmi Rezi, Lalu; Ali, Ibrahim (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2024)
This study examines waste management at the Bintaro TPS, Ampenan, which receives 30 m³ of waste daily. The aim of the research is to analyze waste management using a SWOT analysis, focusing on utilizing household waste by the community. The results of the IFAS and EFAS analysis show a score of 3.26 for strengths and 1.26 for weaknesses, indicating that strengths and opportunities outweigh weaknesses and threats. Based on these results, the proposed strategy is an aggressive strategy (SO) to optimize waste management with current land and facility limitations. The study also emphasizes the importance of collaboration between the government, community, and the private sector to address the waste problem in the Ampenan District.